When did weaving become a male profession? - Øye, Ingvild (Danish Journal of Archaeology, 2016)
The article discusses the development and technological changes within weaving in the Middle Ages when it developed into a major craft and one of the most important industries of the Middle Ages in Northern Europe. While prehistoric weaving appears as a predominantly female work domain, weaving became a male profession in urban contexts, organised within guilds. Hence, it has almost become a dogma that the expanding medieval textile industry, and corresponding transition from a female to a male work domain, was caused by new technology – the horizontal treadle loom. By utilising various source categories, documentary, iconographic and archaeological evidence, the article substantiates that the conception of the medieval weaver as a male craftsman should be adjusted and the long-established dichotomy between male professional craftsmen and weavers, and women as homework producers of textiles should be modified, also when related to guilds. The change from a domestic household-based production to a more commercially based industry took place at different times and scales in various areas of Europe and did not only involve men.